Kepemilikan Keluarga Sebagai Pemoderasi Dampak Komite Audit dan Kualitas Audit Pada Agresivitas Pajak - Ananda, Marisa Julia; Sumaryati, Anna (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The objectives of the research include the influence of audit committees, the audit quality of companies, and family ownership as a moderating factor against tax aggressiveness. Banking companies listed on the Indonesian Stock Exchange (BEI) between 2018 and 2022 are the subject of this study. This data is obtained from the annual reports of 46 banking companies. Samples are selected using purposive sampling techniques, and the WarpPLS 8.0 program is used to process and analyze data. The results showed that the audit committee has the ability to reduce the level of tax aggressiveness. On the contrary, the quality of the audit does not affect the tax aggressivity. Moreover, family ownership can not strengthen the negative influence of the auditor committee on the tax agresiveness, but family ownedness can reinforce the negative impact of audit quality on tax agressiveness.